Complete Modern C++ - Lone, Umar (Packt Publishing, 2020)
Learn the new C++ 11, 14, and 17 features with the most comprehensive C++ tutorial About This Video Become proficient in modern C++ (C++11/14/17) Explore different STL components and create amazing applications Understand both old and new C++ concepts In Detail In this course, you will explore C++ and get to grips with the modern features introduced in C++11, 14, and 17. C++ is a general-purpose programming language developed by Bjarne Stroustrup in 1979, and it still is one of the most popular programming languages used for creating high-performance applications across a wide variety of domains and platforms. This course will help you learn C++ as an object-oriented language with modern features, covering both old and new C++ concepts with clear examples. You will start with basic language features that were used to build complex programs, including classes, operator overloading, composition, inheritance, polymorphism, templates, and concurrency. The course will then delve into the assembly to help you understand concepts better.